Hurricane Wave Loads on Spar-Type Floating Wind Turbines: A Comparison of Simulation Schemes - Shaopeng Li; Teng Wu (Atmosphere, 2023)
Floating wind turbines are sensitive to hurricane events. Since the turbine rotors are parked and the blades are feathered during hurricanes, the aerodynamic loads due to boundary-layer winds are relatively small compared to the hydrodynamic loads due to sea surface elevations. Hence, accurate modeling of the hurricane wave loads is crucial to ensure the safety of floating wind turbines. During a hurricane, large wave heights with severe flow separation make it inaccurate to use either linear panel method-based models (without nonlinear consideration associated with fluid viscosity) or Morison equation-based models (without unsteady consideration associated with fluid memory). Efforts have been made to advance simulation schemes of hurricane wave loads on spar-type floating wind turbines. This study systematically compares and assesses the efficacy of six hydrodynamic models available in the literature along with a newly proposed model. The ability of these seven hydrodynamic models to capture nonlinear and/or unsteady effects is investigated. As a demonstration example, the wave loads on a spar-type wind turbine are calculated using these seven models to highlight the underlying role of each simulation scheme in accurately acquiring the dynamic responses of this type of offshore floating structure in severe hurricane seas. It is found that the nonlinear viscous term in the Morison equation and hybrid model serves as an important nonlinear damping mechanism. The reduction of the low-frequency wave load and added mass in the modified hybrid model collectively leads to larger displacements compared to those based on the hybrid model. While the displacements based on the stretching method and Rainey’s equation are similarly larger than those based on the Morison equation, their nonlinear wave loads are much smaller than those in FNV theory.